Morphometric analysis of central incisor and Its association to periodontal phenotypes In indian population - P. DIVYASHRE; P. CHETNA; P.S.G. PRAKASH; S. SANGEETHA; DJ VICTOR (International Journal of Pharma and Bio Sciences, 2017)
The diagnosis of the Periodontal disease at the earliest would arrest and reverse the condition, whereas identification of a forerunner could prevent its occurrence. The purpose of this study was to analyze the relationship between the crown morphology and the gingival biotype based on the individual's ethnicity among the Indian population.A total of 49 healthy individuals with 25 North Indians and 24 Dravidian populations were recruited for the study. Clinical measurements, including the width and the height of maxillary central incisor crowns, the apico-incisal height of the keratinized mucosa (KM), the buccal gingival thickness (BGT), the depth of the sulcus (SD) and the height of the inter proximal maxillary central papilla (Ph), were investigated in both the population. The maxillary central incisor crown was grouped as triangular, square and square tapered based on its shape. The morphology of the crown was analyzed if there are any significant differences among groups in its relation to the buccal gingival thickness. The mean buccal gingival thickness was increased for square shaped teeth that are 2.09 ± 0.20mm and 2.10 ± 0.22mm respectively in the North Indian and the Dravidian Population. But this does not demonstrate any significant differences compared to square tapered or triangular shaped tooth form for both the population. There is association between gingival biotype and shape of teeth but the study could not demonstrate any statistically significant differences.